The Relationship of Culture-Based Primary Service with Patient Satisfaction in the Inpatition Room of Hospital X in Pontianak - Margaretha Wilyana; Tri Ardayani; Juliyanti Juliyanti (CV Media Inti Teknologi, 2024)
The aim of this research is to analyze the relationship between culture-based excellent service and patient satisfaction in the inpatient room at Hospital X in Pontianak.The research uses quantitative descriptive methods with a cross-sectional study approach. The total sample is 86 respondents, the measuring instrument is a questionnaire of excellent service and customer satisfaction which was created by the author himself with validation results of calculated r values ranging from 0.40 to 0.887 and reliability of 0.944 and 0.956. The research results showed that almost all of the respondents said it was very good, 68 people or (79.07%), the level of patient satisfaction, the majority of respondents said it was very satisfied, 63 people or (73.26%), the results of the analysis of excellent service relationships based on Culture and patient satisfaction with the Spearman Rank obtained a SIG value = 0.000 (Sig < 0.05), so it can be concluded that there is a very significant relationship between excellent service and patient satisfaction in the Inpatient Room at Hospital X in Pontianak. It is hoped that the results of this research can be used to improve excellent nursing service because of the importance of excellent nursing service in increasing the satisfaction of inpatients at Hospital X in Pontianak.